Disparities in Secondary Prevention of Atherosclerotic Heart Disease After Coronary Artery Bypass Grafting in Northern Plains American Indians - Hannah Kruger; Christopher Zumwalt; Donald Warne (Mary Ann Liebert, 2019)
Introduction: Cardiovascular disease has become the leading cause of death in American Indians (AIs). For patients with severe disease requiring coronary artery bypass grafting (CABG), AIs have been demonstrated to present with increased risk factors. Guideline-directed medical therapy after CABG effectively reduces mortality and recurrent ischemic events in all patients and is especially important in high-risk populations such as AIs. Methods: Isolated CABG patients between 2012 and 2017 were studied and 74 AI patients were identified. Propensity matching was performed and the resulting 148 patients were followed for a year after surgery. Guideline-directed medical therapy (GDMT) for secondary prevention of atherosclerotic disease after CABG was detailed in all patients. Results: GDMT was similar between groups (85% AI vs. 89% non-AI; p=NS), and the incidence of prescribed antiplatelet medications, beta-blockers, and statins was similar. AIs were more likely to receive insulin therapy (p=0.002) and opioids (p=0.03) at discharge, while non-AIs were more likely to receive anti-arrhythmic medications (p=0.002). One year after discharge, GDMT trended lower in AIs (75% AI vs. 85% non-AI; p=0.2) and AIs were less likely to be on a statin 1 year after surgery (81% AI vs. 93% non-AI; p=0.04). Opioid use trended higher after 1 year in AIs (28% AI vs. 18% non-AI; p=NS) and fewer AI patients participated in cardiac rehabilitation (CR) after CABG. Conclusions: Disparities in GDMT for secondary prevention of coronary artery disease after CABG exist, with fewer AI patients receiving statins and undergoing CR 1 year after surgery. Increased use of opioids in AIs is troubling and deserves further investigation. Improved adherence to GDMT would be expected to improve long-term outcomes after CABG in this high risk population.